2017
DOI: 10.1002/jcp.26071
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of in vitro model of corneal scar pathophysiology

Abstract: Corneal scarring is the major source of permanent blindness worldwide. The complex pathophysiology of corneal scarring is not comprehensibly understood as it involves the interaction of a constellation of pro-fibrotic cytokines influencing several signaling pathways involved in corneal scar development. In the present study, an attempt has been made to generate a relatively simple in vitro corneal scar model using primary corneal keratocytes by exogenously providing an optimized dose of combination of cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
(96 reference statements)
0
16
0
Order By: Relevance
“…In particular, the 3D bioprinted lung-like structures could be ideal in studying respiratory infections as they provide an air–tissue interface in complex, hollow architecture composed of multiple layers and cell types, which is far-fetched by traditional tissue engineering methods. In our laboratory, we have successfully fabricated various in vitro healthy 71 and diseased 72 tissue models using silk fibroin-gelatin bioink laden with specific cell types. These models closely recapitulated native tissues and ECM ultrastructure.…”
Section: Physiologically Relevant In Vitro Models—mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the 3D bioprinted lung-like structures could be ideal in studying respiratory infections as they provide an air–tissue interface in complex, hollow architecture composed of multiple layers and cell types, which is far-fetched by traditional tissue engineering methods. In our laboratory, we have successfully fabricated various in vitro healthy 71 and diseased 72 tissue models using silk fibroin-gelatin bioink laden with specific cell types. These models closely recapitulated native tissues and ECM ultrastructure.…”
Section: Physiologically Relevant In Vitro Models—mentioning
confidence: 99%
“… 19 Tissue engineering strategies can provide innovative solutions and can be well applied in this vicious situation involving a constellation of unknown questions. Tissue engineering can be employed for the development of a healthy tissue model (such as human hair follicle, 20 cartilage tissue 21 ) as well as a diseased tissue model (osteoarthritis model, 22 ophthalmic pathological condition 23 , 24 ), etc. Three-dimensional bioprinting enables even more advancements, as it entails the layer-by-layer specific positioning of the living cells, biochemistry, growth factors, orientation of ECM, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These models include manual circular keratectomy, incisional, and excimer laser induced models in rodents and rabbits (Wilson et al, ; Stepp et al, ; Ljubimov and Saghizadeh, ; Miyagi et al, ). Researchers have also developed ex vivo models using organ‐cultured corneas to study corneal fibrosis (Karamichos et al, ; Karamichos et al, ; Chawla and Ghosh, ). Chemical injuries have been used to look at fibrosis (Hamill et al, ; Gordon et al, ; Baradaran‐Rafii et al, ; Panahi et al, ).…”
Section: Lessons Learned From the Study Of The Corneamentioning
confidence: 99%
“…Chemical injuries have been used to look at fibrosis (Hamill et al, ; Gordon et al, ; Baradaran‐Rafii et al, ; Panahi et al, ). Advances in cell and organ culture methodology are leading to models that are used to study both formation and resolution of fibrotic foci (Karamichos et al, ; Chawla and Ghosh, ) as shown in Figure A (Sriram et al, ).…”
Section: Lessons Learned From the Study Of The Corneamentioning
confidence: 99%
“…Clinical outcomes after photorefractive keratectomy (PRK) have been reported for up to 19 years and have confirmed, especially for myopia lower than 6.0 diopters (standard error of the mean [ SE ]), that the procedure is predictable, stable, and safe (Alió et al, ; Bricola, Scotto, Mete, Cerruti, & Traverso, ; Chawla & Ghosh, ; Chi & Trinkaus‐Randall, ; Guerin, Darcy, O'connor & O'Keeffe, ; Rajan, Jaycock, O'Brart, Nystrom, & Marshall, ; Vestergaard et al, ). However, compared with the long‐term clinical follow‐up data available, the structural corneal data obtained through in vivo confocal microscopy (IVCM) are, to our knowledge, limited to the first 5 years after PRK (Cruzat, Qazi, & Hamrah, ; Erie, McLaren, Hodge, & Bourne, ; Gambato et al, ; Guthoff, Zhivov, & Stachs, ; Linna & Tervo, ; Moilanen, Vesaluoma, Müller, & Tervo, ).…”
Section: Introductionmentioning
confidence: 99%